Gestión del almacén de insumos para mejorar el sistema de inventarios de la empresa pesquera Exalmar S.A.A. - Sede Chicama 2018 - Acuña Jara, Cesar Edder (2018)
This research work has been developed with the purposes of show that the management of the input warehouse improves the inventory system of "Pesquera Exalmar com pany, Chicama headquarters. For the present investigation the descriptive - transversal design was used, as well as the methods: deductive-inductive, analytical, synthetic and statistical method. In the datum collection techniques, it was used the survey with the objective of extracting the information from the source because the personnel involved know the critical points where it should be improved. When make the contextual diagnosis based on the foregoing, it was identified that the Exalmar company needs to improve the inventory process due to they don't have procedures and updated standards that facilitate to carry out the work in a structured and organized manner, It is permitting so the improvement of the warehouse management, among the most relevant observations are the following: inadequate cyclical counts, lack of updating and improvement of the operations and functions manual, the existence of a register of entry and exit of materials in its Kardex was not evidenced, deficient order of the materials of the warehouses. Also, there is no adequate traceability that refers to the monitoring of products delivered directly to other users, having inefficient control of the products that reach the company. In this research was carried out to qualification and characterization of warehouse management in the company. This is very important to carry out the control of the products that have a greater impact to the cost of the inventories that permit have information of the existing products. More correct. These results were the basis for proposing actions that permit to improve the management of inventories, this proposal consists in Carry an exact record of the demand, and analysis of its variability, in order to preserve the levels of existence of appropriate products in the warehouse. Carry an exact record of the demand, and analysis of its variability, in order to preserve the levels of existence of appropriate products in the warehouse. To make internal audits to detect time, inconveniences and new problems in the different departments, for to establish corrective measures on time. Therefore, it was concluded that the management of the input warehouse contribute to improve the inventory system of the "Pesquera Exalmar" company S.A.A. Chicama headquarters.